Vector Bond Graph Method of Kineto- static Analysis for Hybrid Driving Five Linkage Mechanism - Wang Zhongshuang; Wang Xifeng (Jixie chuandong, 2016)
For improving the reliability and efficiency of the kineto- static analysis for hybrid driving linkage mechanism,the corresponding vector bond graph method is proposed. Based on the kinematic constraint condition of planar translational joint,the more concise vector bond graph model of planar translational joint is built. According to the adjacency relationship of the components of hybrid driving five bar linkage mechanism,the vector bond graph model of hybrid driving five bar linkage is established by assembling the vector bond graph model of planar moving rigid body,revolute joint and translational joint. For the algebraic difficulties brought by differential causality and nonlinear junction structure in automatic modeling and dynamics analysis of this kind mechanism,the effective bond graph augment method is proposed. Based on this,the unified equations of system driving moment and constraint force at joints are derived,which are more concise and practical.As a result,the computer aided kineto- static analysis of hybrid driving five bar linkage system is realized. By a practical example system,the reliability and validity of the proposed method is illustrated.